The birth of the American horror film - Rhodes, Gary Don, 1972- (Edinburgh University Press, 2018)
Explains how the American horror movie came into existence. Although early cinema has long been a key area of research in film studies, the origin and development of the horror film has been a neglected subject for what is arguably one of the world's most popular film genres. Using thousands of primary sources and long-unseen illustrations, 'The Birth of the American Horror Film' examines a history that begins in colonial Salem, taking an interdisciplinary approach to explore the influence of horror-themed literature, theatre and visual culture in America, and how that context established an amorphous structural foundation for films produced between 1895 and 1915. Exhaustively researched, bridging scholarship on Horror Studies and Early Cinema, 'The Birth of the American Horror Film' is the first major study dedicated to this vital but often overlooked subject. Suitable for use on courses focusing on Film History, Genre and Horror.